Selective depletion of metastatic stem cells as therapy for human colorectal cancer - María Virtudes Céspedes; Ugutz Unzueta; Anna Aviñó; Alberto Gallardo; Patricia Álamo; Rita Sala; Alejandro Sánchez‐Chardi; Isolda Casanova; María Antònia Mangues; Antonio Lopez‐Pousa; Ramón Eritja; Antonio Villaverde; et al. (EMBO Molecular Medicine)
Abstract Selective elimination of metastatic stem cells (MetSCs) promises to block metastatic dissemination. Colorectal cancer (CRC) cells overexpressing CXCR4 display trafficking functions and metastasis‐initiating capacity. We assessed the antimetastatic activity of a nanoconjugate (T22‐GFP‐H6‐FdU) that selectively delivers Floxuridine to CXCR4+ cells. In contrast to free oligo‐FdU, intravenous T22‐GFP‐H6‐FdU selectively accumulates and internalizes in CXCR4+ cancer cells, triggering DNA damage and apoptosis, which leads to their selective elimination and to reduced tumor re‐initiation capacity. Repeated T22‐GFP‐H6‐FdU administration in cell line and patient‐derived CRC models blocks intravasation and completely prevents metastases development in 38–83% of mice, while showing CXCR4 expression‐dependent and site‐dependent reduction in foci number and size in liver, peritoneal, or lung metastases in the rest of mice, compared to free oligo‐FdU. T22‐GFP‐H6‐FdU induces also higher regression of established metastases than free oligo‐FdU, with negligible distribution or toxicity in normal tissues. This targeted drug delivery approach yields potent antimetastatic effect, through selective depletion of metastatic CXCR4+ cancer cells, and validates metastatic stem cells (MetSCs) as targets for clinical therapy.